L-carnitine enhances excretion of propionyl coenzyme A as propionylcarnitine in propionic acidemia. - Roe, C R (1984)
Treatment with L-carnitine greatly enhanced the formation and excretion of short-chain acylcarnitines in three patients with propionic acidemia and in three normal controls. The use of fast atom bombardment mass spectrometry and linked scanning at constant magnetic (B) to electric (E) field ratio identified the acylcarnitine as propionylcarnitine in patients with propionic acidemia. The normal children excreted mostly acetylcarnitine. Propionic acidemia and other organic acidurias are characterized by the intramitochondrial accumulation of short-chain acyl-Coenzyme A (CoA) compounds. The substrate specificity of the carnitine acetyltransferase enzyme and its steady state nature appears to facilitate elimination of propionyl groups while restoring the acyl-CoA:free CoA ratio in the mitochondrion. We suggest that L-carnitine may be a useful therapeutic approach for elimination of toxic acyl CoA compounds in several of these disorders.